Some aspects of improving the methodology for assessing creditworthiness of the borrower (Journal of Economic Research & Business Administration, 2016)
Currently, the domestic practice, there is no single, universal methodology for assessing the creditworthiness of the borrower. Its formation is difficult, as the credit quality assessment involves an analysis of a wide range of quantitative and qualitative indicators. Meanwhile, the development and improvement of its own system of assessing the creditworthiness of customers is an important task of each credit institution that seeks to work with stable reliable partners. Currently used and recommended ways of assessing creditworthiness based mainly on the analysis of data on the borrower in the previous period. For all the importance of this assessment it can not exhaustively characterize the creditworthiness of the borrower in the coming period. It is advisable to use a forecasting creditworthiness of the borrower in the coming period, in order to make an informed decision on granting loans. In assessing creditworthiness should take into account the forthcoming changes in market conditions.
Keywords: Credit; creditworthiness; analysis of credit; borrower; assessment; credit policy.